The Effects of Relationship with Family and Friends on the Household Reporting of Arrears - Dang, Hang (2016)
The increasing level of household debt in the UK has raised significant concerns over the financial stability at household level, especially as a result of the financial crisis in 2008/09. High household debt level could potentially impact the households’ ability to meet financial obligations and the sustainability of the economy. This paper is going to explore the effects of relationship with family and friends on the household probability of falling into arrears with housing costs, council tax and household bills payments, which is believed to initially signal potential financial difficulties at household level. The research analyses a data set of 8,616 households from the wave 5 of a longitudinal study Understanding Society, which reflects the 21st century life in the UK. The findings suggest that strong relationships with family and friends reduce the household probability of failing to meet financial commitments, while disappointment in relationships with family and friends leads to households being more likely to fall into arrears. In particular, understanding and reliability from family and friends, as well as the ability to share worries with family and friends most significantly decrease the household likelihood of arrears in mortgage and rental payments.